Нэр томьёоны бодлого: Terminology policies - A., Enkhtuya (Mongolian Journal of Foreign Languages and Cultures, 2023)
This article illustrates modern tendency of terminology, concept on terminology policy as a part of language policy, terminology applications and products, terminology planning, international aspects of terminology work, different categories of organization and network as well as some units responsible for terminology affairs in Mongolia and the necessity of policy to provide the coherence of terminology-related affairs in Mongolia.